Antibacterial Activity and MIC-MBC Evaluation of Active Fraction from Paederia foetida Linn. Leaves Against Infectious Pathogenic Bacteria - Melda Yunita; Muhamad Sadam Safutra; Is Ikhsan Hataul; Siti Nur Azizah; Rosida Rosida (Biology, Medicine, & Natural Product Chemistry, 2026)
Antibacterial resistance remains a global health concern, prompting exploration of natural plant-based alternatives. This study aimed to evaluate the antibacterial activity of the active fraction from Paederia foetida Linn. leaves against six infectious pathogenic bacteria: Staphylococcus aureus, Bacillus subtilis, Shigella dysenteriae, Salmonella typhi, Cutibacterium acnes, and Enteropathogenic Escherichia coli (EPEC). Kirby-Bauer disk-diffusion method was used to measure inhibition zones and the broth dilution method to determine Minimum Inhibitory Concentration (MIC) and Minimum Bactericidal Concentration (MBC). Results showed that the active fraction exhibited variable antibacterial activity, with the highest inhibition zones recorded against E. coli (6.5 mm), B. subtilis (6.0 mm), and S. dysenteriae (5.0 mm) at 100% concentration. The MIC values ranged from 125 µg/mL (for B. subtilis) to 500 µg/mL (for S. aureus and C. acnes), while MBC values ranged from 250 µg/mL to 1000 µg/mL, confirming bacteriostatic to mild bactericidal effects, particularly toward B. subtilis and E. coli. Compared to the crude extract we reported previously, the fraction displayed lower inhibitory activity, suggesting that the antibacterial effect of P. foetida may rely on synergistic interactions among multiple secondary metabolites present in the whole extract. These findings indicate that the active fraction of P. foetida leaves possesses potential antibacterial properties, suggesting that further studies should focus on exploring synergistic effects among fractions and confirming antibacterial efficacy through in vivo evaluation.